Gender differences in applying for STEM programs in higher education: Evidence from a policy shift in Hungary - Koen Declercq; Joris Ghysels; Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2018)
We study how admission policies in higher education affect enrollment decisions of men and women and the decision to apply to STEM programs. More specifically, we investigate how an increase in the relative acceptance probability for STEM programs affects these decisions. We apply our analysis to Hungary and we evaluate a policy reform that limited access to subsidized non-STEM programs. We find that this change in the selectivity of the admission system differently affected application decisions of men and women. After the reform, fewer students applied to higher education and the reform especially discouraged the participation of women. After the reform, more men and women applied to STEM programs or non-subsidized non-STEM programs in which they have to pay tuition fees. This last effect is stronger for women. As the reform affected the chance to be admitted to higher education, we estimate a structural model to analyze how the responsiveness to admission probabilities in application decisions differs between men and women. We find that women are more sensitive to admission probabilities. Finally, we use the model to simulate the impact of alternative admission policies on enrollment in STEM programs. We find that an open access policy in STEM programs would stimulate more men and women to apply to these programs.
Keywords: I21; I23; I24; J16; J24; 330; higher education; admission; gender differences; STEM; structural model